Efektivitas Unit Usaha Pesantren dalam Pemberdayaan Ekonomi Masyarakat Sekitar(Studi pada Pondok Pesantren Tebuireng Jombang) - Ficky Nor Arifin; Peni Haryanti (Hikamatzu | Journal of Multidisciplinary, 2024)
Tebuireng Islamic Boarding School, as an Islamic educational institution with a long history and prestige in Indonesia, has taken progressive steps to integrate religious education with efforts to empower the surrounding community's economy through the Tebuireng Skill Training Center (TPKU Tebuireng). This research aims to determine the effectiveness of the business unit owned by Tebuireng Boarding School in promoting the economic empowerment of the surrounding community. This study employs a qualitative descriptive research method with in-depth interviews conducted with the management of the boarding school's business unit, participants, and the local community. The research findings indicate that TPKU Tebuireng has provided a positive impact on the local economy. TPKU Tebuireng operates effectively as it has achieved empowerment goals, maintains harmony among all members, and adapts to the needs of the surrounding environment